Reconstruction of an indigenous community's belief in dragon; Research on prehistoric Batu Naga Site in Kuningan, West Java - Akbar, Ali (UI Scholars Hub, 2017)
Archaeological remains can be used as data to reconstruct the culture of the past. At the top of Mount Tilu, Kuningan, stands a menhir decorated with reliefs. The indigenous community which once cared for this site has long vanished. This paper is the result of a research applying archaeological method and semiotic interpretation to reconstruct the life of this long-dead indigenous community. The reliefs on the menhir tell of the beliefs of this ancient which venerated the dragon. They considered this creature as the beginning of life on the earth. This dragon is different from its counterparts known in other parts of the world.